Somerset and Cambridge Streets, ca. 1960 - Neiley, Robert (Tufts Archival Research Center, 2005)
Street-level view north of Somerset Street looking towards Cambridge Street. Buildings line both the east-southeast and west-northwest sides of Somerset Street, which are visible along the left and right sides of the photograph. Other buildings line the north side of Cambridge Street and are included in the background of the photograph. Signage adorns some of the buildings, and automobiles line both Somerset and Cambridge Streets. 7 5/8 x 9 9/16, 8 x 10 overall Photographs